"Hello, World!": Starting a Coding Group for Librarians. Issue 3 (2nd July 2016) - de la Cruz, Justin; Hogan, Joshua
Abstract : Column description. The Technology column examines current and developing technology topics in libraries. The column's focus is creative uses of technology, introductions to new technologies, and critiques of current technologies, their uses, or their future. Readers interested in contributing ideas or writings to this column may contact column co-editors Suzanne Townsdin and Susan Whitmer.